2015
DOI: 10.1111/jep.12463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a protocol‐based intervention to promote timely switching from intravenous to oral paracetamol for post‐operative pain management: an interrupted time series analysis

Abstract: Following implementation, immediate decrease in utilisation and costs (p<0.05) and a trend change over the follow-up period were observed. Average monthly reduction was 26% (95%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…The annual cost reduction by these strategies was estimated in that study to be £15 100 (equivalent to 5.8 trillion Iranian rials) . Similarly, another multifaceted, protocol‐based intervention to ensure timely switching from intravenous to oral paracetamol achieved a notable reduction in the utilisation and costs of PP in the first 5 months after its implementation …”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The annual cost reduction by these strategies was estimated in that study to be £15 100 (equivalent to 5.8 trillion Iranian rials) . Similarly, another multifaceted, protocol‐based intervention to ensure timely switching from intravenous to oral paracetamol achieved a notable reduction in the utilisation and costs of PP in the first 5 months after its implementation …”
Section: Discussionmentioning
confidence: 91%
“…7 Similarly, another multifaceted, protocol-based intervention to ensure timely switching from intravenous to oral paracetamol achieved a notable reduction in the utilisation and costs of PP in the first 5 months after its implementation. 8 The success of evidence-based protocols in changing physicians' practise seems to depend on many factors, and improving the prescription of medicines through protocols requires both initial enforcement and continuous effort. It is now generally accepted that, in developing countries, protocols should be developed and implemented by the pharmacist for each level of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This switch is usually well‐described for antimicrobials, as it is part of the antimicrobial stewardship programs . Several interventions have proven efficiency in promoting this switch, such as staff training, new documentation system, staff feedback, or new guidelines . It has also been reported that regular interventions, instead of a 1‐shot intervention, are necessary to get long‐lasting effect on IV to PO conversion …”
Section: Introductionmentioning
confidence: 99%